Cover Image: Volume 82 Issue 8. Issue 8 (22nd April 2022) - Mao, Fengyi; Kong, Yifan; Liu, Jinghui; Rao, Xiongjian; Li, Chaohao; Donahue, Kristine; Zhang, Yanquan; Jones, Katelyn; Zhang, Qiongsi; Xu, Wei; Liu, Xiaoqi
Abstract : Cover Caption: The cover image is based on the Original Article Diptoindonesin G antagonizes AR signaling and enhances the efficacy of antiandrogen therapy in prostate cancer by Fengyi Mao et al., https://doi.org/10.1002/pros.24336